‎The future prospects of Islamic banking in ‎Tunisia An empirical survey - Echchabi, Abdelghani; Azouzi, Dhekra; Abd. Aziz, Hassanuddeen (Emerald Publishing Limited, 2016)
Islamic banking services, and the factors that might influence their decision. Design/methodology/approach – A total of 100 questionnaires were randomly distributed to Tunisian banking customers. structural equation modelling and one sample t-test were subsequently applied. Findings – The results revealed that the attitude dimensions have a significant impact on the Tunisian customers’ intention to adopt Islamic banking services. On the other hand, the results have also shown that the Tunisian customers are willing to shift to Islamic banking services. Originality/value – These findings have significant contributions that are discussed thereinafter. Keywords Structural equation modelling, Islamic banking, Tunisia, Theory of planned behaviour